Magnitude of ST-Segment Elevation in Acute Inferior Myocardial Infarction and the Proximity of Right Coronary Artery Lesion (Bangladesh Heart Journal, 2023)
Background & objective: Involvement of the right coronary artery frequently occurs in acute inferior myocardial infarction. Typical ECG changes in this condition involve ST-segment elevation in inferior leads. The present study was intended to predict the site of the lesion in the right coronary artery (RCA) in patients with acute inferior wall myocardial infarction using the height of ST-segment elevation as the predictor variable.Methods: The present cross-sectional study was carried out in the Department of Cardiology, National Institute Cardiovascular Diseases (NICVD), Dhaka, Bangladesh over a period of one year between July 2010 to June 2011. Patients with acute inferior myocardial infarction admitted to CCU of NICVD within 12 hours of the onset of chest pain and underwent coronary angiography within 4 weeks of acute myocardial infarction (AMI) were the study population. With the help of a 12-lead ECG, magnitudes of ST-segment elevation in leads II, III, and aVF were measured. The highest degree of stenosis along the RCA revealed by an angiogram was accepted as the culprit lesion. The right coronary artery was divided into proximal (from its ostium to the origin of the RV branch), mid (from the RV branch to the acute marginal branch), and distal (from the acute marginal branch onward) parts. The sum of ST-segment elevation was then computed and compared among the three groups of patients divided on the basis of the site of lesion in RCA.Result: The findings of the study showed that nearly half (48%) of the patients had lesions in the proximal, 38% in the mid, and the rest (14%) in the distal part of the right coronary artery (RCA). While patients with proximal lesions had the highest mean sum of the ST-segment elevation (12.1 ± 0.6 mm), those with distal lesions had the lowest mean sum of the ST-segment elevation (6.1 ± 0.2 mm). The three groups were significantly heterogeneous (p < 0.001). The magnitude of STsegment elevation in Lead II, III, and aVF and the sum of ST-segment elevation all were significantly higher in patients with proximal lesions than those in patients with mid and distal lesions (p < 0.001).Conclusion: The magnitude of ST-segment elevation can predict the site of lesion in RCA in inferior wall myocardial infarction. The greater the height of STsegment elevation, the higher the probability of lying the lesion in the proximal part of the RCA.Bangladesh Heart Journal 2023; 38(1): 58-62